(untitled) (Bangladesh Journal of Neuroscience, 2015)
Background: The relation between serum lipids and ischemic stroke remains controversial in young patients. The aim was to determine the serum lipid profile and the vascular risk factors for ischaemic stroke in a series of patients under 45 with an ischemic stroke and to compare them with a series of controls of the same age. Material and method: This case-control study was conducted in the Department of Neurology and Department of Biochemistry of BSMMU, Dhaka, between the period of July 2007 and June 2009 for duration of two years. A total number of 50 patients presented with recent ischemic stroke and 50 control person were enrolled in this study. All patients of both sexes, aged between 15 to 45 years presented with ischemic stroke, from 0 day to 1 month that was confirmed by CT scan of head/MRI of brain. Vascular risk factors were recorded and blood sample was collected from the cases and the controls and analyzed at the Dept. of Biochemistry, BSMMU for estimation of serum fasting lipid profile. Result: Multivariate analyses showed that other than serum lipids- family history of dyslipidaemia, family history of stroke or TIA, history of HTN and smoking habit are found significant risks for stroke in young adult. Conclusion: The present study does not confirm the role of serum lipids as risk factors for ischemic stroke in young adult. Other than serum lipids- family history of dyslipidaemia, family history of stroke or TIA, history of HTN and smoking habit are found significant risks for stroke in young adult. Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 56-64